Potato viruses in Finland and their identification - Kurppa, Aarne (Agricultural and Food Science, 1983)
The occurrence of potato viruses in Finland and alternative methods for their identification are reported in this study. The following seven viruses were found to occur; potato viruses X, S, M, Y, A, potato leaf roll virus (PLRV) and tobacco rattle virus (TRV). The isolates of potato viruses X and Y included two clearly distinct strains. The other viruses had only minor variants. The most severe and important of the viruses was PVY, particularly its Y° strain. Other important viruses were PVM and PVA and potentially PLRV. PVY was found to be the most easily transmitted in the field. For serological identification of the viruses, indigenous antisera produced for selected isolates were mostly used. Significant serological variation was only found among the PVY isolates. The lowest concentration of PVX D-protein detected with the agar gel double diffusion test was 10 µg/ml and 1 µg/ml with the single diffusion test. With the ELISA test 0.1 ng of virus /ml could be detected. For PVX the lowest relative value detected in potato leaf sap was a dilution of between 10-6 and 10-7. The chloroplast agglutination test was too unreliable for detecting PVY in potato samples. Also the agar gel double diffusion test was found to be too insensitive for the identification of potato viruses but the single diffusion test could be used in certain cases. With the ELISA test potato viruses X, S, M and Y could be reliably detected in potato leaf sap and with almost the same accuracy in sap from sprouting tubers. The ELISA test was also found to give satisfactory results during routine testing for the identification of PVA and PLRV in potato leaves or non-dormant tubers.